Functional Recovery of Rare Case of Sciatic Nerve Schwannoma with Peripheral Nerve Block and without Intraoperative Neurophysiological Monitoring - Jefri Henky; Ahmad Faried (Faculty of Medicine, Universitas Padjadjaran, 2020)
Schwannoma are benign peripheral nerve tumors derived from the Schwann cells in the neural sheath. Sciatic nerve schwannoma in the lower extremity is uncommon, accounting for only 1% of all schwannoma cases. This report aimed to describe the functional recovery after lower limb surgery of sciatic nerve schwannoma with peripheral nerve block and without intraoperative neurophysiological monitoring (IOM) performed in Semen Padang Hospital in 2019. A 78-year-old woman presented with a complaint of pain on her slowly growing mass at the right popliteal region, which had existed for 22 years. Microsurgical resection was performed with local peripheral nerve block and without intraoperative neurophysiological monitoring. Tumor was removed en-bloc by sharp dissection using a microscope without any complication. The patient had significant pain relief without any neurologic deficit three weeks after the surgery. Penyembuhan Secara Fungsi Kasus Langka Schwannoma Saraf Sciatic dengan Blok Saraf Perifer Tanpa Pemantauan Neurofisiologis Intraoperatif Schwannoma adalah tumor saraf tepi jinak yang berasal dari sel Schwann dalam selubung saraf. Pada ekstremitas bawah, schwannoma saraf sciatic jarang terjadi, terhitung 1% dari semua schwannoma. Laporan ini bertujuan menggambarkan pemulihan fungsional dengan blok saraf perifer setelah operasi tungkai bawah schwannoma saraf sciatic tanpa pemantauan neurofisiologis intraoperatif (IOM) di Rumah Sakit Semen Padang, 2019. Seorang wanita 78 tahun datang dengan keluhan nyeri pada massa yang tumbuh perlahan di daerah popliteal kanannya selama 22 tahun. Reseksi bedah mikro dilakukan dengan blok saraf perifer secara lokal dan tanpa pemantauan neurofisiologis intraoperatif. Tumor terangkat secara en-bloc dengan diseksi tajam menggunakan mikroskop tanpa ada komplikasi. Pada minggu ketiga pascaoperasi, pasien mengalami pengurangan rasa sakit yang signifikan tanpa defisit neurologis.